2010
DOI: 10.1242/jcs.063784
|View full text |Cite
|
Sign up to set email alerts
|

Meteorin promotes the formation of GFAP-positive glia via activation of the Jak-STAT3 pathway

Abstract: SummaryMeteorin is an orphan ligand which has been previously reported to control neuritogenesis and angiogenesis, as well as gliogenesis.However, the precise function of this factor in CNS development and the underlying molecular mechanisms are poorly understood. Here, we demonstrate that meteorin is involved in GFAP-positive glial differentiation through activation of the Jak-STAT3 pathway, by using neurosphere and retinal explant culture systems. During embryonic brain development, meteorin is highly expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 30 publications
5
47
0
2
Order By: Relevance
“…However, the cellular receptor(s) for meteorin are still unknown. It has been reported that meteorin acts through the Jak‐STAT3 pathway to promote glial differentiation in neural stem cells (Lee, Han, Lee, Park, & Kim, 2010). However, exogenous treatment of astrocytes with meteorin did not activate the same pathway (Lee et al, 2015).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…However, the cellular receptor(s) for meteorin are still unknown. It has been reported that meteorin acts through the Jak‐STAT3 pathway to promote glial differentiation in neural stem cells (Lee, Han, Lee, Park, & Kim, 2010). However, exogenous treatment of astrocytes with meteorin did not activate the same pathway (Lee et al, 2015).…”
Section: Potential Therapeutic Targets In Astrocytesmentioning
confidence: 99%
“…In the adult mouse brain, METRN is detected in ubiquitously distributed astrocytes, Bergmann glia, and a few discrete neuronal populations (Nishino et al, 2004;Jorgensen et al, 2009). Meteorin has been implicated in the regulation of axonal extension and glial cell differentiation (Nishino et al, 2004;Lee et al, 2010) and in angiogenesis (Park et al, 2008). Additionally, administration of METRN protects striatal neurons from excitotoxicity caused by quinolinic acid in vivo (Jorgensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Primary NSCs were cultured from E13.5 mouse embryos, as described previously (12). Briefly, embryos were dissected from pregnant female mice (Samtako) and neurospheres were allowed to form in complete neurobasal medium (Invitrogen Life Technologies) containing 2% B27 (Invitrogen Life Technologies), human epidermal growth factor (20 ng/ml, R&D Systems, Minneapolis, MN, USA), and basic fibroblast growth factor (10 ng/ml, Invitrogen Life Technologies) for 4 days, by plating neuroepithelial cells on non-coated culture dishes.…”
Section: Methodsmentioning
confidence: 99%
“…The predominant source of meteorin in the adult brain are astrocytes, and meteorin is known to promote glial cell differentiation and the expression of GFAP in NSCs (12,17); therefore, the present study aimed to demonstrate that meteorin was involved in the reactive gliosis process. The expression levels of meteorin were analyzed in reactive astrocytes from a photothrombotic (PT) ischemia mouse model, as well as following stimulation of transforming growth factor (TGF)-β, which led to the activation of astrocytes in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation